O problema da demarcação em Popper, Kuhn e Laudan - Carvalho, Robson Rodrigues (2017)
The general goal of this dissertation is to discuss the demarcation problem, analysing the perspectives offered by Karl Popper, Thomas Kuhn, and Larry Laudan. So as to achieve that goal, the dissertation comprises three chapters. In first, we reconstruct the demarcation problem in Popper’s epistemology. We analyse his early reflections, exploring the emphasis given in this period to the demarcation pro-blem as essentially aiming at the separation of science and pseudocience. We then examine the de-marcation problem as it appears in the polemical exchange between Popper end logical positivists. The second chapter analyses what Kuhn has to say on the demarcation problem, and compares his thoughts to Popper’s. The third chapter presents Laudan’s main arguments against the legitimacy of the problem. The concluding section of the dissertaion maintains that: (i) Popper managed to present a legitimate philosophical problem, although his solution is not satisfactory, and (ii) Laudan was competent at laying out harsh criticisms of the demarcation problem, but was too rushed by claming its demise. The main reason for these two mistakes lies in the assumptions held by both, especially that of thinking the a satisfactory or legitimate answer to the problem must present a single criterion for scientificity.